2016
DOI: 10.1017/s000712341600017x
|View full text |Cite
|
Sign up to set email alerts
|

On the Frontline Every Day? Subnational Deployment of United Nations Peacekeepers

Abstract: Research has shown that United

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 44 publications
3
62
0
Order By: Relevance
“…55 C.f. Ruggeri, Dorussen, and Gizelis 2016. statistically significant at the 95% level. 56 In Model 2, we distinguish between one-sided violence by government and rebel actors, since our discussion suggests that the deployment mechanisms may look different as peacekeepers are more constrained in intervening against government abuses.…”
Section: Non-random Deployment Of Peacekeepersmentioning
confidence: 84%
“…55 C.f. Ruggeri, Dorussen, and Gizelis 2016. statistically significant at the 95% level. 56 In Model 2, we distinguish between one-sided violence by government and rebel actors, since our discussion suggests that the deployment mechanisms may look different as peacekeepers are more constrained in intervening against government abuses.…”
Section: Non-random Deployment Of Peacekeepersmentioning
confidence: 84%
“…Empirical studies on peacekeeping need to tackle the problem that peacekeepers are not randomly deployed; usually, the most violent conflicts and locations host peacekeepers (Fortna ; Gilligan and Stedman ; Ruggeri, Dorussen, and Gizelis ). This is problematic when one wants to assess the effect of peacekeeping on political violence.…”
Section: Empirical Strategymentioning
confidence: 99%
“…This is due to two reasons: first, previous research has shown that international actors like the UN tend to engage in the most severe cases, where third party guarantees are most needed due to the severity of the conflict or the deep cleavages between the conflict parties (Ruggeri, Dorussen, & Gizelis, 2016). This means that chances of peace are lower from the outset than in countries where conflict is less severe.…”
Section: Graph 1 -Ssr In Conflict and Transitional Countries (In Percmentioning
confidence: 99%